Examining value co-creation in healthcare purchasing: a supply chain view - Chakraborty, Samyadip; Dobrzykowski, David (Business: Theory and Practice, 2014)
Healthcare providers are under intense cost and quality pressures. Extant literature indicates that healthcare’s unique operational context necessitates collaboration, but suffers from factors that inhibit coordination. At the same time, general views on value creation are evolving toward a servicedominant logic (SDL) view, which focuses more intently on collaborations aimed at the sharing of specialized competencies among actors functioning in a network. This study while highlighting the challenges faced in healthcare supply chain provides a contemporary view of value creation based on competencies and SDL and attempts at proposing a theoretical framework traversing along the boundaries of Prahalad and Ramswamy’s (2004) DART framework. This study conceptualizes supply chain management practices along the DART framework and puts forth the logical arguments to establish DART SCM practices as enablers of value cocreation.